Penyelesaian Sengketa Waris yang Berkeadilan pada Masyarakat Adat Suku Kajang Kabupaten Bulukumba - Akib, Muhammad Kibar; Koeswahyono, Imam; Sulistyarini, Rachmi (Universitas Negeri Malang, 2022)
This study aimed to analyze the obstacles to the settlement of inheritance disputes in the Kajang indigenous people and the efforts to settle inheritance disputes in a just manner in the Kajang indigenous peoples. The type of research used in this study was empirical juridical with an anthropological approach—sources of data obtained from primary and secondary legal materials. Data collection techniques were carried out through interviews. The data obtained were analyzed using descriptive methods. The results of this study indicated that the obstacles to the settlement of inheritance disputes in the Kajang indigenous people were the parties making false confessions, insisting on defending their rights and social status, tending to be emotional, and lacking firmness from the mediator. Efforts to settle inheritance disputes that were fair to the indigenous people of the Kajang tribe are carried out based on local wisdom based on pasang ri kajang through three stages, namely deliberation at the hamlet head level, mediation by the village head, and the customary justice institution.